Water quality in Indonesia: The role of socioeconomic indicators - Andi Kustanto (Jurnal Ekonomi Pembangunan, 2020)
Population growth and the construction of settlements and industrial estates continue to increase at an unprecedented rate that has created gains and losses on environmental quality. The trend of population growth shows a declining trend but is not directly proportional to the fluctuating water quality index over the past ten years. The study uses secondary data with the quantitative approach using the panel data Fixed Effect Model (FEM) with Generalized Least Squares (GLS) to examine socioeconomic indicators in 34 provinces on water quality in Indonesia. Through analysis in this study shows that explanatory variables of the number of population and population density have a negative and significant effect on water quality in Indonesia of 4.69 and 1.95—ceteris paribus. The control variables of the number of establishments of micro and small scale manufacturing industry, and a group of workers, GRDP per capita, and realization of foreign direct investment show negative and significant results on water quality in Indonesia. It indicates that environmental management in Indonesia experiences a higher pressure from the utilization of ecological resources compared to efforts to improve the environment itself. Whereas household control variables of households and improve sanitation, the volume of water distributed by water supply establishment and the squared of GRDP per capita show positive and significant results on water quality in Indonesia, which shows that this is evidence of the government's success in managing the environment better.